The Use of Full-Line Forcing Contracts in the Video Rental Industry - Ho, Katherine; Ho, Justin; Mortimer, Julie Holland (American Economic Review, 2012)
Bundling is at the forefront of many policy debates as new technologies allow firms to implement more complex bundling arrangements. Realistic analyses of bundling—particularly between suppliers and retailers—require detailed data on both supply arrangements and consumer demand. We analyze firms' use of bundling as a vertical restraint (known as full-line forcing) using extensive supply and demand data from the video rental industry. Our model captures key details of the market that determine firms' contractual choices, and sheds light on the implications of these decisions. The empirical approach provides a model for how to analyze bundling when detailed data are available. (JEL D86, L14, L81, L82)